Studi Histologi dan Histomorfometri Daging Sapi Bali dan Wagyu (HISTOLOGYCAL AND HISTOMORPHOMETRY STUDY OF BALI CATTLE AND WAGYU BEEF) - Suwiti, Ni Ketut; Suastika, I Putu; Swacita, Ida Bagus Ngurah; Besung, I Nengah Kerta (Jurnal Veteriner; Vol 16 No 3 (2015), 2015)
The objective of this study was to detect histological structure and histomorphometry of bali cattleand wagyu beef. The samples were collected from rib eye muscle of wagyu and bali cattle. The tissuesamples were fixed, dehydrated and embedded in paraffin and 4-5 mm sections, for histological examinationand stained with Haematoxilin-Eosin (HE). The light binocular microscope was used to identify the samples.The study showed that the beef histological structure consisted of: cells / muscle fibers, fatty and connectivetissues. The muscle fibers of wagyu were observed larger, regular, and longer compared to the Bali cattle.Additionally, intramuscular fat cells and connective tissue interlobulus were found less and thinner thanthe Bali cattle. In the area of muscle where the longitudinal cut was done, its observed that the presence ofI and A bands in Bali cattle beef were clearer compared to the wagyu. The diameter muscle fibers of balicattle beef (45.00 ±1.94 ?m), was smaller (P < 0.01) compared to the wagyu (75.00±1.82 ?m), as well as fatcell size of bali cattle beef (90.10 ±2.13 ?m) and wagyu beef (195.00±2.57?m). In conclusion, the structureof histology and histomorphometry of rib eye muscle in Bali cattle were different to the wagyu.
Keywords: histological structure, histomorphometry, beef, Bali cattle, wagyu cattle